Genetic polymorphisms of ACE I/D, IL-1β G > A and IL-4 VNTR among Egyptian subjects with rheumatoid arthritis. (4th May 2022) - Elshazli, Rami M.; Elsaid, Afaf M.; Shawky, Doaa M.; Barakat, Lamiaa A. A.
Abstract: Background: Various reports examined the contribution of ACE I/D, IL-1β G > A and IL-4 VNTR with the susceptibility to RA but with conflicting findings. The goal of this study is to assess the impact of these three variants with the susceptibility, clinical and biochemical markers in addition to different composite indices of RA. Subjects and Methods: This case-control survey enclosed 120 RA Egyptian patients who were emulated with 150 healthy controls from the same territory. Their genomic DNA was genotyped utilising the PCR approach. Results: RA patients with ACE allele (D) and IL-4 VNTR allele (2 R) were expressively higher emulated with healthy controls ( p  < .05). Nevertheless, RA patients with IL-1β (A allele) failed to achieve an apparent significant emulated with healthy controls ( p  > .05). Conclusions: This work specifies a noteworthy association for ACE I/D and IL-4 VNTR but not IL-1β G > A polymorphisms with RA susceptibility among Egyptian subjects.